Cytokine and Antimicrobial Peptide Levels in Cholelithiasis - K. F. Gasimova (Клінічна хірургія)
Objective. To study the cytokines and antimicrobial peptides concentrations in patients with cholelitiasis during 1 year treatment before and after the surgery.